Relación entre obesidad y déficit cognitivo en pacientes con diabetes mellitus tipo 2 - Pazos Zavaleta, Carlos Alberto (2019)
Introduction: Diabetes mellitus type 2 is disease that produce macrovascular and microvascular complications. The cognitive impairment is situation associated to diabetes mellitus type 2. So, there are several factors implicated, like obesity. Objective: To determinate the relationship between obesity and cognitive impairment in patients with diabetes mellitus type 2. Material and methods: Descriptive and transversal study, it has 149 patients the belong Control Program about Diabetes of HRDT. It has been estimated the association between obesity (BMI ≥ 30 kg/m2) and cognitive impairment (MMSE<24) in patients with diabetes mellitus type 2. Results: The 14.77% of the patients with diabetes mellitus type 2 had cognitive impairment. While 26.17% presented obesity. On the other hand, 23.08% of the patients with obesity manifested cognitive impairment, whereas only in 11.82% of the non-obese patients cognitive deficit was detected, being these values not significant, for a level of significance of p <0.05. Conclusions: Obesity and cognitive deficit are not significantly associated in patients with type 2 diabetes mellitus.